AKTUALISASI METODE PROBING PROMPTING OLEH GURU FIQIH DI MAS NUR IBRAHIMY - Panjaitan, Putri Fadilah; Fattah, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Participation and develop critical thinking skills in understanding Islamic legal concepts. However, Fiqh instruction is still predominantly characterized by lecture-based approaches that limit students' involvement in the learning process. This study aimed to analyze the actualization of the probing prompting method by Fiqh teachers at MAS Nur Ibrahimy, identify the challenges encountered in its implementation, and describe students' responses toward the use of this method. This study employed a qualitative approach using a field research design. Data were collected through observation, interviews, and documentation involving Fiqh teachers and students as research informants. Data validity was ensured through source triangulation and technique triangulation, while data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings revealed that the Fiqh teacher actualized the probing prompting method through the use of introductory questions, probing questions, and prompting questions delivered in a gradual manner. The implementation of this method created a more interactive learning environment, increased students' participation, and facilitated a deeper understanding of Fiqh materials. The challenges encountered included limited participation of some students, differences in academic abilities, and time constraints during instruction. Meanwhile, students demonstrated positive responses toward the implementation of the probing prompting method, as it enhanced their confidence in expressing opinions, encouraged active involvement in learning activities, and fostered critical thinking skills. Therefore, the probing prompting method can serve as an effective alternative instructional strategy to improve the quality of Fiqh learning in madrasahs.